Russula darjeelingensis, a new species from Eastern Himalaya, India - Paloi, Soumitra; Das, Kanad; Acharya, Krishnendu (Phytotaxa, 2018)
Russula darjeelingensis is characterized by its small sized white pileus with a tall and narrow stipe, white spore print, basidiospores with amyloid suprahilar spot and a pileipellis containing encrusted pileocystidia and absence of primordial hyphae. The combination of all these characters and molecular phylogenetic analyses of internal transcribed spacer sequences of nuclear ribosomal DNA confirmed it as a new species in genus Russula Pers., subg. Russula Romagn. emend. sect. Polychromae (Maire) Sarnari subsect. Paraintegrinae Sarnari. A comprehensive morphological description, illustrations, and comparisons with morphologically similar and phylogenetically related species are provided in the present study.